PRIMAL INSTINCTS AND SOCIETAL CONSTRUCTS: A THEMATIC STUDY OF WILLIAM GOLDING'S LORD OF THE FLIES - Fatah, Shokhan Mohammed; Saeed, Yadgar Faeq (Universitas Islam Sumatera Utara (UISU), 2024)
This qualitative study investigates the portrayal of human nature's mystique through theoretical analysis. Using a fabulist, mythological approach, William Golding delves into the complexities of human psychology. This study explores the novel's thematic examination of civilization and savagery, demonstrating how the boys' descent into chaos reflects both innate human wickedness and the fragility of social conventions. By analyzing characters, symbols, and narrative structures, the research clarifies the intricate relationship between civilization and barbarism through the lens of primal instincts and societal norms. The study reveals that Golding's depiction of human psychology effectively illustrates the tension between civilization and savagery. The primary text analysis shows how Golding portrays fundamental human characteristics, highlighting the inherent darkness within and the struggle to maintain societal order. Secondary sources are also carefully examined to support this argument. The significance of this study lies in its depiction of the duality of human nature as represented in the novel, offering insights into the delicate balance between our civilized veneers and underlying primal instincts.